METHODOLOGICAL RECOMMENDATIONS FOR TEACHERS TO FOSTER READING HABITS THROUGH ENGLISH STORIES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The formation of reading habits is an essential component of modern education, particularly in the field of foreign language teaching. Reading enables learners to acquire linguistic knowledge, broaden their worldview, and develop analytical thinking skills. However, contemporary students often demonstrate a declining interest in reading due to the growing influence of digital media and entertainment technologies. In this regard, educators are required to employ teaching approaches that not only improve language competence but also stimulate students’ willingness to read independently. English stories can serve as an effective pedagogical instrument for achieving these goals because they combine educational content with emotional engagement and personal involvement. This article discusses the role of English stories in the development of reading habits and provides methodological recommendations for teachers seeking to encourage regular reading among learners. Particular attention is paid to story selection, classroom organization, interactive reading techniques, and learner-centered activities that contribute to sustained reading motivation.
Keywords: reading habits, English stories, reading motivation, extensive reading, storytelling, learner autonomy, literacy development, English language teaching.